The effect of transformational leadership on young lecturer innovation capacity in Shandong higher education - Hua, Zhang; Mohd Noor, Mohd Asri (Journal of Islamic, Social, Economics and Development, 2026)
This research examines the effect of transformational leadership encompassing inspirational motivation, individualized consideration, intellectual stimulation, and idealized influence on the innovation capacity of young lecturers in higher education institutions in Shandong. Innovation capacity is examined through four dimensions includes domain-relevant skills, creativity-oriented processes, motivational drivers, and supportive environments. This study is quantitative research used questionnaire.100 Young lectures in Shandong Province involved in this study. The data collected were analyzed by descriptive statistics, correlation test and multiple regression analysis to measure the relationship between transformational leadership practices and young lecturers’ innovation capacity. Results showed that there existed a positive correlation close to 0.8 between transformation leadership and innovation ability of young lectures. The Pearson correlation coefficient was r = 0.612 (p =. 001 with a statistically significant association. This relationship is also confirmed by additional simple linear regression analysis. Innovation Capacity is predicted by transformational leadership at 37.5% (R² = 0.375) with an adjusted R² of 0.363 and a standard error of the estimate of 0.550. A good predictive relationship of R = 0.612 attests to the strong relationship exactly exhibited by this prediction. Greater perceived transformative leadership among lecturers was positively related to innovation. This report highlights the necessity for universities to implement transformational leaderships traits, such as collaboration, intellectual stimulation and individualized consideration. Developing such environments has potential to provide a positive impact on the innovativeness of lecturers. These findings add to the literature on university leadership and provide actionable direction for policy-makers and academics.